Emerging problems of antibiotic resistance in community medicine - Parasakthi, N. (Cambridge University Press, 1996)
Emergence of antimicrobial resistance in bacteria associated with community acquired infections has made the choice of empirical therapy more difficult and more expensive. The problems due to possible spread of MRSA to the community, emergence of penicillin resistance in S. pneumoniae, ampicillin resistance in H. influenzae, and multiresistance among common enteric pathogens are highlighted. Bacteria have a remarkable ability to develop resistance to many of the newly synthesized antimicrobial agents but the appropriate use of antibiotics will delay and in many cases prevent the emergence of resistance.